2007
DOI: 10.1227/01.neu.0000249210.89096.6c
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral-Mediated Gene Transferinto the Canine Brain in Vivo

Abstract: NIH Public Access Author ManuscriptNeurosurgery. Author manuscript; available in PMC 2007 November 27. Published in final edited form as:Neurosurgery. 2007 January ; 60(1): 167-178. NIH-PA Author ManuscriptNIH-PA Author Manuscript NIH-PA Author Manuscript transgenes elicited immune-mediated long-term survival in a syngeneic intracranial GBM model in rodents. However, the lack of a large GBM animal model makes it difficult to predict the outcome of therapies in humans. Dogs develop spontaneous GBM that closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
(90 reference statements)
0
10
0
1
Order By: Relevance
“…Common therapeutic strategies include suicide gene therapy, oncolytic treatment, immunomodultion, gene replacement, proapoptotic treatment, and antiangiogenesis 175, 203. Successful delivery or efficacy of gene therapy approaches using viral vectors and plasmid DNA has been shown experimentally in canine brain tumor cells and brain using adenoviral,204, 205, 206, 207, 208, 209 retroviral201, 202, 210 herpes,211 and adeno‐associated viral212, 213, 214 delivery. Few viral therapies have progressed to phase III clinical trials, and none have been shown to have significant efficacy in high‐grade brain tumors in phase III trials to date 175…”
Section: Novel Therapiesmentioning
confidence: 99%
“…Common therapeutic strategies include suicide gene therapy, oncolytic treatment, immunomodultion, gene replacement, proapoptotic treatment, and antiangiogenesis 175, 203. Successful delivery or efficacy of gene therapy approaches using viral vectors and plasmid DNA has been shown experimentally in canine brain tumor cells and brain using adenoviral,204, 205, 206, 207, 208, 209 retroviral201, 202, 210 herpes,211 and adeno‐associated viral212, 213, 214 delivery. Few viral therapies have progressed to phase III clinical trials, and none have been shown to have significant efficacy in high‐grade brain tumors in phase III trials to date 175…”
Section: Novel Therapiesmentioning
confidence: 99%
“…This allows performing preclinical trials that will mimic more closely the clinical scenario, in which new therapies are applied in patients that simultaneously undergo traditional treatment. We and others have previously demonstrated the feasibility of delivering therapeutic transgenes to dog GBM cells in vitro and dog brain cells in vivo upon intracranial injection of gene therapy vectors, such as type 5 adenoviral vectors [69-71], adeno-associated viral vectors [72], plasmid DNA/polyethylenimine (PEI) complexes [71], which suggests that dogs bearing spontaneous GBM would be a suitable model to test novel gene therapy approaches. Importantly, the availability of canine GBM J3T [70, 73] and W&W [74] cell lines allows in vitro screening of novel therapeutic agents before moving to preclinical trials in dogs bearing spontaneous GBM.…”
Section: Animal Models For Preclinical Testingmentioning
confidence: 99%
“…Also, considering the requirement of exogenous nucleotide analogs to induce cell death, the withdrawal of the pro-drug could stop the development of putative adverse side effects. Our previous results indicate that administration of Ad-TK in the naïve brain of rats [20] and dogs [69-71] does not significantly alter the structure of the normal brain and induces only a mild, transient local inflammation. Importantly, it has been demonstrated that injection of adenoviral vectors encoding HSV1-TK into the margins of the tumor cavity after GBM surgical resection followed by GCV administration was well tolerated in over 70 patients in 6 early clinical trials [2].…”
Section: Pro-apoptotic Gene Therapy Targetsmentioning
confidence: 99%
“…Ad-expressed transgenes were detected utilizing custom-generated rabbit antibodies specific to TK 35,44,45 or human soluble Flt3L 19,30,31,44 (developed in rabbit; 1:1,000) combined with the mouse antivimentin antibody. Alexa 488 directly conjugated fluorescent secondary antibodies (1:1,000) were used to detect transgenes (Invitrogen, Carlsbad, CA, USA).…”
Section: Human Soluble Flt3l Elisamentioning
confidence: 99%